HUBUNGAN PENERAPAN KONSEP KONSERVASI LINGKUNGAN HIDUP DAN TINGKAT SOSIAL EKONOMI DENGAN PENGETAHUAN LINGKUNGAN PADA SISWA KELAS III SDN KALANGAN TAHUN PELAJARAN 2014/2015 ( Studi Sekolah Dasar menuju Adiwiyata ) - Heru Purwoko; Peduk Rintayati; Siti Supeni (Universitas Sebelas Maret (UNS), 2016)
The purpose of writing a thesis is to determine: 1)The relationship between the application of the concept of environmental conservation through cooperative learning Picture and Picture with knowledge of the environment of students in third grade primary school students Among No. 184 towards school Adiwiyata Mandiri. 2) The relationship between socio-economic levels with the knowledge of the environment of students in Class III Elementary School Among No. 184 towards school Adiwiyata Mandiri. 3) The relationship between the application of the concept of environmental conservation through cooperative learning Picture and Picture and socioeconomic levels together with knowledge of the environment of students in Class III Elementary School Among No. 184 towards school Adiwiyata Mandiri. This type of research is a quantitative approach. Research subjects were 21 students of class III SDN Among the school year 2014/2015. The results showed 1) There is a relationship between the application of the concept of environmental conservation through cooperative learning Picture and Picture with knowledge of the environment of students in third grade students of SD Negeri circles with significant value 0.002> 0.05, 2) There is a relationship between socio-economic levels with the knowledge of environment student in third grade students of SD Negeri circles with significant value 0.001 <0.05, and 3) There is a relationship the application of the concept of environmental conservation through cooperative learning Picture and Picture and socioeconomic levels together with knowledge of the environment of students in class III SD Negeri circles known Fhitung> Ftabel = 22.60> 3.15. Keywords: Cooperative Learning, Social Economics, School Adiwiyata